1989
DOI: 10.1111/j.1469-7998.1989.tb02498.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth rate of the tarsometatarsus bone in birds

Abstract: Twisting and bending deformities of the long limb bones of growing birds are common. In domestic poultry they are associated with rapid growth. In order to examine the variation in bone growth rates amongst the Class Aves as a step towards learning about the aetiology of growth deformities, we collected data on this and several other variables from a large sample of species. Adult tarsometatarsal length (ATL) was proportional to adult weight (W)0.36. The exponent did not differ significantly from 1/3. Mean leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 54 publications
(3 reference statements)
1
33
0
3
Order By: Relevance
“…A high degree of ossification has been suggested to improve locomotor performance, as well as the structural integrity of the skeleton (Kirkwood et al, 1989;Arendt and Wilson, 2000). S. mollissima ducklings can dive and procure their own food within 24 h of hatching.…”
Section: Life History and Ossification Sequencementioning
confidence: 99%
“…A high degree of ossification has been suggested to improve locomotor performance, as well as the structural integrity of the skeleton (Kirkwood et al, 1989;Arendt and Wilson, 2000). S. mollissima ducklings can dive and procure their own food within 24 h of hatching.…”
Section: Life History and Ossification Sequencementioning
confidence: 99%
“…Terminal BCO presents as necrotic degeneration and bacterial infection primarily within the proximal head (articular cartilage or epiphysis, growth plate or physis, and metaphysis; Figures 1 and 2) of the femur and tibiotarsus (hereafter referred to as the tibia), but also in the growth plates of other bones that are subjected to severe torque and shear stress, such as the fourth thoracic vertebrae (e.g., spondylopathy or spondylitis). The fourth thoracic vertebrae in birds articulate as the flexible pivot or fulcrum between the fused vertebrae of the notarium cranially and the bony pelvis caudally (Carnaghan, 1966; Wise, 1971; Nairn and Watson, 1972; Nairn, 1973; McCaskey et al, 1982; Kibenge et al, 1983; Mutalib et al, 1983a; Griffiths et al, 1984; Duff, 1990a; Pattison, 1992; Riddell, 1992; Thorp et al, 1993b; Thorp, 1994; Thorp and Waddington, 1997; McNamee et al, 1998; Butterworth, 1999; McNamee and Smyth, 2000; Bradshaw et al, 2002; Dinev, 2009; Stalker et al, 2010; Wideman et al, 2012). High incidences of both femoral and tibial BCO lesions (Figure 3) have been observed in lame broilers from commercial flocks.…”
Section: Introductionmentioning
confidence: 99%
“…Kirkwood et al (1989a) and Kirkwood, Spratt & Duignan (1989b) demonstrated that tarsometatarsal bone elongation was greater in altricial compared with precocial bird species, and that the rate of avian bone elongation was highly correlated with the size of the cartilaginous growth zones. Moreover, Carrier & Leon (1990) suggested that maximum growth rate of skeletal elements is determined by the interplay between mechanical function and the rate at which ossified tissue can be deposited.…”
Section: Introductionmentioning
confidence: 99%